Perlindungan terhadap Nasabah Akibat Serangan Ciber: Studi di Bank Syariah Indonesia KC Pekalongan Pemuda - Utami, Ghifari Wulandari; Saifudin; Akhmad Nurasikin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Cyber ​​attacks have a significant impact on the banking sector. One of the cyber attack incidents occurred at Bank Syariah Indonesia (BSI), including at the BSI Pekalongan Pemuda Branch Office (KC). The attack was marked by disruption of digital services, such as BSI Mobile, ATM machines, and teller services that could not be accessed by customers. This incident reflects the potential for bank negligence in carrying out its obligations to protect customer systems and data. This study aims to analyze the implementation of legal protection for customers due to cyber attacks, as well as to examine the legal consequences arising from the negligence of BSI KC Pekalongan Pemuda in anticipating cyber threats. This study is a juridical-empirical study with a qualitative approach. Data were collected through field studies, including interviews with related parties at BSI KC Pekalongan Pemuda, as well as literature studies covering legal literature, laws and regulations, and legal doctrines. The conceptual and legislative approaches were used to analyze the legal basis for customer protection and the bank's legal responsibility for cyber attacks. The results of the study show that customers are given the right to file a complaint with the Financial Services Authority (OJK) if they experience losses due to cyber attacks. The cyber attack that occurred at BSI KC Pekalongan Pemuda resulted in various legal and non-legal consequences, namely violations of the Personal Data Protection Act, violations of contractual obligations between the bank and customers, potential sanctions from authorities, the possibility of claims for compensation from customers, and losses to the bank's reputation.